Mysterious quad of constrictive pericarditis, recurrent pleural effusions, bone involvement and interstitial lung disease. Issue 3 (29th March 2019) - Ding, Feihong; Chahine, Johnny; Deshwal, Himanshu; Ghosh, Subha; Tan, Carmela; Simpfendorfer, Conrad; Cremer, Paul; Jellis, Christine; Arrossi, A Valeria; Klein, Allan L
Abstract: Erdheim–Chester disease (ECD) is a rare multisystemic non-Langerhans cell histiocytic neoplasm. The rarity of the disease and heterogenous clinical presentations often leads to delayed diagnosis. Historically, ECD lacked effective treatment and the prognosis was poor. Following the recent discovery of frequent BRAF-V600E mutation in patients with ECD, vemurafenib, a selective BRAF V600 kinase inhibitor has been approved for BRAF-mutated ECD patients. The prognosis of ECD has dramatically improved with early recognition of the disease and available treatment. ECD affects nearly every organ system. Cardiac involvement with pericardial effusion is common but rarely with constrictive physiology or requiring pericardiectomy. We present a case of a 56-year-old woman with recurrent pericarditis with constrictive physiology along with pleural effusion and interstitial lung disease that was diagnosed with ECD 3 years after initial presentation. The patient's symptoms were relieved with pericardiectomy and targeted therapy.